Consideration of Congestion Situations in Telecommunication Networks and Methods of Their Processing as a Special Type of Emergency Situations - Hamlet H. Harutyunyan; Hmayak A. Avanesyan (Изд-во НАН РА)
This article discusses the methods of struggle with congestion situations in telecommunication networks, considering them as a special type of emergency situations, which frequently occur in computing systems.
Keywords: Mathematics; Computer software